Implementation of Vijeo Citect in SCADA-Based Industrial Plant Level and Pressure Control - Yusman; Zaqiul Zambi; Aidi Finawan (Universitas Serambi Mekkah, 2024)
Implementing an efficient control system in modern industry requires proper integration between SCADA (Supervisory Control and Data Acquisition) software, PLC (Programmable Logic Controller) control, and measurement parameters such as level and pressure. This thesis aims to investigate the implementation of Vijeo Citect software in SCADA-based level and pressure control using Twido PLC control to control field devices related to level and pressure. Vijeo Citect software is configured to monitor and control the system in real-time, as well as integrate data from the Twido PLC to analyze and respond to desired level and pressure parameters. The results of this research illustrate that the implementation of Vijeo Citect in level and pressure control using the Twido PLC as a controller provides an effective and responsive solution. When the surface level is 0% (0 cm), the level transmitter emits a current of 3.85 mAmp and the pressure transmitter emits a current of 3.9 mAmp and when the surface level is 90% (60cm) the level transmitter produces a current of 5.65 mAmp while the pressure transmitter produces a current of 7.81 mAmp with a pressure of 2.5 bar after closing the solenoid valve.